2000
DOI: 10.1021/ac000266o
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Sugar Compounds in Olive Plant Extracts by Anion-Exchange Chromatography with Pulsed Amperometric Detection

Abstract: We describe a chromatographic method that uses isocratic elution and pulsed amperometric detection to determine soluble carbohydrates in plant tissues. Such a method provides a rapid and convenient means to obtain a complete profile of the sugar components of leaves and roots from olive (Olea europaea L. cv. Coratina) plants. A simple purification of plant extracts using pure water was developed, which is far less time-consuming and retains a high level of accuracy. Excellent separation of myo-inositol, galact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(45 citation statements)
references
References 21 publications
3
41
0
1
Order By: Relevance
“…The relatively low amount of sucrose compared to mannitol, especially in leaf tissues, suggests that sucrose in olive trees is an initial product of photosynthesis mainly translocated from sources to sinks, and does not play a significant role as an osmolite or storage compound, at least in leaves. Low leaf sucrose was also reported by Tattini, Gucci, Romani, Baidi, & Everard (1996) and Cataldi et al (2000). In leaf, NOE and PC had above average sucrose, whereas OM had below average sucrose (Figure 2A).…”
Section: Resultssupporting
confidence: 69%
“…The relatively low amount of sucrose compared to mannitol, especially in leaf tissues, suggests that sucrose in olive trees is an initial product of photosynthesis mainly translocated from sources to sinks, and does not play a significant role as an osmolite or storage compound, at least in leaves. Low leaf sucrose was also reported by Tattini, Gucci, Romani, Baidi, & Everard (1996) and Cataldi et al (2000). In leaf, NOE and PC had above average sucrose, whereas OM had below average sucrose (Figure 2A).…”
Section: Resultssupporting
confidence: 69%
“…In fact, the contribution of passive π represents approximately 60% of the total osmotic adjustment, while the remaining 40% is due to active π (Table 3). The ex-novo synthesis of osmolytes takes place in both leaves and roots of the olive tree and regards mainly carbohydrates and the aminoacid proline (Cataldi et al, 2000). Extracts of leaves and roots of well-watered olive revealed that the most predominant carbohydrates are mannitol and glucose, which account for more than 80% of the total soluble carbohydrates.…”
Section: Osmotic Adjustment and Cell Wall Propertiesmentioning
confidence: 99%
“…myo-inositol, galactinol, mannitol, galactose, glucose, fructose, sucrose, raffinose and stachyose [20]. …”
Section: Analyte(s)mentioning
confidence: 99%